Oxidative damage to membrane lipids in the thyroid – no differences between sexes. (2nd November 2021) - Stepniak, Jan; Lewinski, Andrzej; Karbownik-Lewinska, Malgorzata
Abstract: It has long been observed that thyroid diseases are more prevalent in women than in men. However, there are limited experimental data demonstrating mechanisms by which sex differences in thyroid diseases may occur and exact molecular mechanisms involved are still far from clear. The aim of the study was to evaluate if there are sex differences concerning oxidative damage to membrane lipids in thyroid homogenates in response to Fenton reaction substrates, i.e., Fe 2+ and/or H2 O2, and, additionally, in response to potentially protective agent, i.e., melatonin. Homogenates of male or female thyroids collected from adult swine ( Sus scrofa domesticus ) at slaughter were incubated in the presence of H2 O2 and/or Fe 2+ without or with addition of melatonin. Malondialdehyde + 4-hydroxyalkenals concentration (LPO index) was measured spectrophotometrically. Neither H2 O2 nor Fe 2+, when used separately, did affect the level of lipid peroxidation in both male and female porcine thyroid homogenates. When H2 O2 (0.5 mM) was used together with different concentrations of Fe 2+, the level of lipid peroxidation increased significantly in both male and female porcine thyroid homogenates, with clear Fe 2+ concentration-dependent stimulatory effect, but without differences between sexes. No sex-specific differences was found concerning oxidative damage to membrane lipids in porcine thyroid in response to Fenton reaction substrates and/or to melatonin. The lack of expected differences may be due to potentially lower sensitivity of membrane lipids comparing to other biological macromolecules to pro-/antioxidative agents in the thyroid. However, further studies should be performed to explain the discussed issue.